2022
DOI: 10.3389/fpls.2022.830840
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Effect of Sucrose Availability and Auxin on Rosa Axillary Bud Metabolism and Signaling, Based on the Transcriptomics and Metabolomics Analysis

Abstract: Shoot branching is crucial for successful plant development and plant response to environmental factors. Extensive investigations have revealed the involvement of an intricate regulatory network including hormones and sugars. Recent studies have demonstrated that two major systemic regulators—auxin and sugar—antagonistically regulate plant branching. However, little is known regarding the molecular mechanisms involved in this crosstalk. We carried out two complementary untargeted approaches—RNA-seq and metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 136 publications
(229 reference statements)
0
5
0
Order By: Relevance
“…Shoot branching is crucial for plant development and yield and is greatly dependent on the ability of axillary buds to grow out along the stem [82][83][84]. Bud outgrowth is very finely regulated by multiple endogenous (e.g., hormones, sugar) and exogenous (e.g., light, water stress) cues [85][86][87][88][89][90][91][92]. In this intricate regulation, sugars behave as signaling entities that promote bud outgrowth through several sugar signaling pathways corresponding to the trehalose 6P-, hexokinase-, glycolysis/tricarboxylic acid (TCA)-, and OPPP-dependent signaling pathways [83,93,94].…”
Section: G6pdhs and Plant Branchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Shoot branching is crucial for plant development and yield and is greatly dependent on the ability of axillary buds to grow out along the stem [82][83][84]. Bud outgrowth is very finely regulated by multiple endogenous (e.g., hormones, sugar) and exogenous (e.g., light, water stress) cues [85][86][87][88][89][90][91][92]. In this intricate regulation, sugars behave as signaling entities that promote bud outgrowth through several sugar signaling pathways corresponding to the trehalose 6P-, hexokinase-, glycolysis/tricarboxylic acid (TCA)-, and OPPP-dependent signaling pathways [83,93,94].…”
Section: G6pdhs and Plant Branchingmentioning
confidence: 99%
“…The authors of [94] first evidenced the role of the OPPP in sugar branching by demonstrating that the promotive effect of sucrose on bud outgrowth is repressed by 6-AN-an inhibitor of G6PDH-in Rosa sp. Molecular experiments conducted on in vitrocultured vegetative buds and on stably transformed Rosa calluses revealed that the OPPPdependent signaling pathway is involved in both sugar-mediated transcriptional (promoter level) and posttranscriptional (3 untranslated region) downregulation of Teosinte Branched 1/Branched1 (TB1/BRC1) [91,94,97]. BRC1 is the main inhibitor of shoot branching [98].…”
Section: G6pdhs and Plant Branchingmentioning
confidence: 99%
“…Glucose has been shown to repress the expression of CKX in Arabidopsis, leading to increased CKs accumulation, which promotes cell division and growth (Choudhary et al, 2022). Sucrose, on the other hand, impacts multiple metabolic pathways in axillary buds, including glycolysis, the TCA cycle, OPPP, and amino acid metabolism (Wang et al, 2022). High concentrations of sucrose have been shown to counteract the inhibitory effects of auxin on axillary buds and stimulate their growth while promoting bud dormancy by rapid transport from the apical meristem (Barbier et al, 2015).…”
Section: Plant Hormones Signals In Regulating Tea Bud Sproutingmentioning
confidence: 99%
“…The changes in nitrogen and carbon supply can alter numerous central metabolites involved in carbon and nitrogen metabolism in parallel (Gao et al, 2020). To support the synthesis of amino acids and ensure adequate growth in rice grain, an appropriate nitrogen content is needed to drive the production of carbon skeletons and provide enough amino acids (Gutiérrez et al, 2007; Wang et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%